Biomechanical evaluation of peripheral nerves after crush injuries. Issue 4 (April 2019) - Wong, Yoke-Rung; Pang, Xin; Lim, Zeus Yiwei; Du, Hejun; Tay, Shian-Chao; McGrouther, Duncan Angus
Abstract: Background: Crush injury of nerves is a common condition but the biomechanical integrity of the human peripheral nerve after crushing is unknown. This study aims to investigate the impact of crush injury on human digital nerves based on different compressive forces. Materials and methods: Twenty digital nerves were harvested from three fresh-frozen cadaver hands. Theoriginal diameters of proximal, middle and distal end of nerve segment were measured. The midst of each digital nerve was compressed by a customized mechanical system, at 1N, 3N and 5N for 30sec. The diameters were measured again within 1 minute after the nerve crush test was performed. The digital nerve was then subjected to biomechanical test to measure its ultimate tensile strength, stiffness, maximum stress and strain. Deformity of digital nerve was computed based on the diameter of middle nerve segment before and after crush test. Results: No significant difference was found in between groups for ultimate tensile strength( p =0.598), stiffness( p =0.593), maximum stress( p =0.7) and strain( p =0.666) . The deformity of nerves under the compression of 1N, 3N and 5N was computed at 72.1%, 54.2% and 45.9%. The effect of compression on the deformity of nerves was statistically significant( p <0.001) . Conclusions: It was found that the compressive forces have no impact on the biomechanical integrity of peripheral nerves but the deformity of nerves could be severely caused by low compressive force. It is suggested that the management of nerve crush injury shall be taken immediately and focus on neurophysiological function and degeneration of nerves for a crush with low compressive force and short duration.